Diagnosis and management of congenital dyserythropoietic anemias. Issue 3 (3rd March 2016) - Gambale, Antonella; Iolascon, Achille; Andolfo, Immacolata; Russo, Roberta
ABSTRACT: Congenital dyserythropoietic anemias (CDAs) are inherited disorders hallmarked by chronic hyporegenerative anemia, relative reticulocytopenia, hemolytic component and iron overload. They represent a subtype of the inherited bone marrow failure syndromes, characterized by impaired differentiation and proliferation of the erythroid lineage. Three classical types were defined by marrow morphology, even if the most recent classification recognized six different genetic types. The pathomechanisms of CDAs are different, but all seem to involve the regulation of DNA replication and cell division. CDAs are often misdiagnosed, since either morphological abnormalities or clinical features can be commonly identified in other clinically-related anemias. However, differential diagnosis is essential for guiding both follow up and management of the patients.